DETERMINANTS ANALYSIS OF NON PERFORMING LOAN USING BANK SPECIFIC VARIABLES AND MACROECONOMIC FACTORS OF 19 COMME`RCIAL BANKS IN INDONESIA - Adi Putra (NIM 19014032 ), Reynold
BankÃ‚Â’s main activity in generating income is by spreading credit. In accordance to that, the credit given by the bank might become Non Performing Loan (NPL), which is a condition when the interest payment is delayed by the agreement. Thus, credit risk is one of the most important risk that are faced by the bank. According to the data by Financial Services Authority, the NPL amount of banks included in BACB 3 and 4 is increasing over the past 5 years. This research attemped to find the relationship between bank specific variables: Bank Size (LNSIZE), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Asset (ROA) and macroeconomic factors: Inflation Rate (INFL), Interest Rate (INTR) and Growth Domestic Product (LNGDP) toward Non Performing Loan (NPL) in 19 commercial banks in Indonesia which is included in BACB 3 and 4 in the period of 2012-2016. The data is processed using panel data regression with Random Effect Method. The result shows that CAR, LDR and LNGDP have positive significant relationship to NPL while LNSIZE, ROA, INFL and INTR have negative significant relationship to NPL. According to the result, the author recommend commercial banks in Indonesia to be more careful in spreading the credit using the funds that have been generated by the bank to improve the credit quality and monitor the significant variable so the amount of NPL can be decreased.